Determination of immunogenicity of an inactivated ND-vaccine developed experimentally with Newcastle disease virus (Genotype VII.2) local isolates of Bangladesh - Mohammad Aynul Haque; Md. Enamul Haque; Mst. Kohinoor Parvin; Md. Mostofa Kamal; Tanbin Rubaiya Islam; Mohammad Sadekuzzaman; Md. Ariful Islam; Mst. Minara Khatun; Muhammad Tofazzal Hossain; Mohammad Asir Uddin; Sham Soun Nahar; A. K. M. Khasruzzaman; et al. (Frontiers in Immunology)
BackgroundNewcastle disease virus (NDV) genotype VII severely affects poultry, causing respiratory and neurological symptoms with a high rate of morbidity and mortality. The research aimed to develop an inactivated ND vaccine using local isolates (Genotype VII.2) and assess its immunogenicity compared to other commercial live ND vaccines.MethodsAn inactivated vaccine using a candidate NDV (GenBank: OR924274.1) was developed according to WOAH guidelines following inactivation, sterility, purity, and safety tests. The birds were vaccinated through subcutaneous (SC) and intramuscular (IM) routes using three doses (0.25, 0.5, and 1.0 ml/bird). Immunogenicity and protective potentiality of the experimentally developed inactivated ND vaccine and live commercial ND vaccine (intra-ocularly/IO) were compared by challenge studies using three vaccination schedules: killed-followed-killed, live-followed-killed, and live-followed-live.ResultsThe birds vaccinated with 1.0 ml/bird SC showed higher antibody titers compared to those of IM-vaccinated groups. Birds vaccinated with the live-followed-killed commercial ND vaccines had slightly higher antibody titers compared to those vaccinated with killed-followed-killed and live-followed-live vaccines. Birds vaccinated with the killed-followed-killed ND vaccine showed a higher protection rate (100%) compared to live-followed-killed (83±5.77%) and live-followed-live (57±5.77%) vaccines. Birds vaccinated with killed-followed-killed group showed a slower decline rate of antibody titers than other groups. This regimen provided significantly better immunity, highlighting its potential in controlling ND outbreaks in Bangladesh's poultry.ConclusionThe study found that the inactivated ND vaccine, developed with the locally circulating isolate of genotype-VII.2 of NDV, might play an important role in effective control and management of ND in the commercial poultry population in Bangladesh.